Comparative housing sale and purchase agreements under the Malaysia, Singapore and New South Wales housing laws - Md Dahlan, Nuarrual Hilal (Universiti Utara Malaysia Press, 2011)
Abandoned housing projects is one of the major problems in housing industry in Peninsular Malaysia.The reasons leading to this problem are many.This catastrophe has caused multifarious problems to the stakeholders, particularly the purchasers who become the aggrieved parties.To date, there is no effective and once-and-for-all means to face the problems of abandoned housing projects.One of the factors which causes abandonment of housing projects in Peninsular Malaysia, is the lack of political will on the part of the government to adopt an affirmative better housing delivery system such as the ‘full build then sell system’ and the introduction of a housing development insurance to face the problems of housing abandonment.This book provides in-depth analysis of the terms and conditions of the statutory standard sale and purchase agreements as enshrined in Schedules G, H, I and J of the Housing Development (Control and Licensing) Regulations 1989.The objective of this book, among others, is to identify the weaknesses of the terms of the agreements, if any, which may have contributed to the problem of abandoned housing projects and their consequential troubles. As comparative analyses, the terms and conditions of the sale and purchase agreements as applicable and enforced in the Republic of Singapore and New South Wales, Australia, are chose.The purpose of these comparative analyses is to find the terms and conditions in these foreign jurisdictions’ agreements which can be learned and adopted in the statutory standard sale and purchase agreements (Schedules G, H, I and J).It is also for the betterment of the Malaysian housing industry as a whole, and to protect the interests of the stakeholders, in particular the purchasers, as against the problems of housing abandonment and its consequences.